Corticolous Lichen Species Association on Shrubs in Temperate Forests of Kumaun Himalaya - Tamta, Ritika; Kumar, Balwant (Indian Forester, 2023)
During the study the maximum 18 corticolous lichen species belonging to 12 genera and five families were recorded from the study area. The best association of lichen species with all growth forms was observed on the shrub Cotoneaster microphyllus Wall. ex Lindl. at high altitude zone. It is situated above 1800m altitude at Moru oak forest (Quercus floribunda Lindl. ex A. Camus) and represented by nine species of lichens. The shrub Berberis petiolaris Wall. ex G. Don is also expressed an instance of shrub species at high altitude region which support to the occurrence of maximum five species of lichens with a good combination of foliose and fruticose forms. The present study is an exploration of the contribution of shrub species which provide a suitable habitat to flourish the lichen species in the area.